Identification and Behavioral Evaluation of Sex Pheromone in Xanthopimpla pedator (Fabricius)—A Serious Pupal Parasitoid of Tropical Tasar Silkworm Anthereae mylitta Drury - Lakshmi Marepally; Gaddam Benarjee (HAYATI Journal of Biosciences, 2016)
Xanthopimpla is a major parasitoid of silk worm cocoons. The female Xanthopimpla pedator(Fabricius) lays the eggs in male cocoons. Control of this infestation with pesticides is not recommended because of its concealed behavior. Various control methods were found to be inefficient. Ecofriendly management is the best strategy that can be applied. We have studied the sex communication in Xanthopimpla pedator (Fabricius), which helps to develop management strategy. Bioassays were done in the laboratory by using olfactometer and pheromone extraction chambers. It was found that female Xanthopimpla produces sex pheromones. The results show a strong attraction of male by female Xanthopimpla. Present results with male and female volatiles also show that female volatiles attract male Xanthopimpla. Fractionation of female volatiles by column chromatography has proven that 20% fraction has highest attraction of males by females.